Genotypes, Antibiotic Resistance, and ST-8 Genetic Clone in Campylobacter Isolates from Sheep and Goats in Grenada - Diana M. Stone; Yogesh Chander; Aschalew Z. Bekele; Sagar M. Goyal; Harry Hariharan; Keshaw Tiwari; Alfred Chikweto; Ravindra Sharma (Veterinary Medicine International)
Rectal swabs from 155 sheep and 252 goats from Grenada were evaluated to determine the prevalence of Campylobacter spp., antibiotic resistance, and multilocus sequence types. Fifteen Campylobacter isolates were obtained (14 C. jejuni and 1 C. coli). The prevalence (3.7%) did not differ significantly between sheep (4.5%) and goats (3.2%). Among the seven antimicrobials tested, resistance was only detected for tetracycline (30.8%) and metronidazole (38.5%). Campylobacter isolates showed no significant difference between sheep and goats for type of antimicrobial resistance or percent of resistant isolates. Twelve of the isolates were successfully genotyped consisting of four recognized clonal complexes and three novel sequence types. Importantly, one isolate from one goat was identified as the C. jejuni sequence type-8, a zoonotic and tetracycline-resistant clone reported to be a highly virulent clone associated with ovine abortion in the USA. Although most samples were from comingled sheep and goat production units, there were no shared sequence types between these two host species. None of the sequence types identified in this study have previously been reported in poultry in Grenada, suggesting sheep- and goat-specific Campylobacter clones in Grenada. This is the first report of genotyping of Campylobacter isolates from sheep and goats in the Eastern Caribbean.